1997
DOI: 10.1046/j.1365-2249.1997.d01-904.x
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of lymphocyte and monocyte activity after intravenous immunoglobulin administration in vivo

Abstract: SUMMARYIn 12 patients with primary hypogammaglobulinaemia we investigated the in vivo effect of one bolus injection (400 mg/kg) of intravenous immunoglobulin (IVIG) on lymphocyte subsets and monocytes in peripheral blood, on plasma levels of soluble factors reflecting monocyte and lymphocyte activity and on lymphocyte proliferation and generation of reactive oxygen species (ROS) from monocytes analysed in vitro. Several immunological changes were induced by IVIG infusion. First, there was a significant decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 32 publications
1
16
1
Order By: Relevance
“…Few reports have studied the effects of intravenous immunoglobulin or anti-D on the generation of ROS. With respect to intravenous immunoglobulin, Aukrust et al 14 demonstrated that intravenous immunoglobulin decreased monocyte ROS production, whereas Nakatani et al 15 showed that intravenous immunoglobulin could significantly enhance ROS in endothelial cells. The reasons for these discrepancies are unknown but may reflect the ability of intravenous immunoglobulins to cause different effects, depending on the cells studied.…”
Section: Discussionmentioning
confidence: 99%
“…Few reports have studied the effects of intravenous immunoglobulin or anti-D on the generation of ROS. With respect to intravenous immunoglobulin, Aukrust et al 14 demonstrated that intravenous immunoglobulin decreased monocyte ROS production, whereas Nakatani et al 15 showed that intravenous immunoglobulin could significantly enhance ROS in endothelial cells. The reasons for these discrepancies are unknown but may reflect the ability of intravenous immunoglobulins to cause different effects, depending on the cells studied.…”
Section: Discussionmentioning
confidence: 99%
“…Possible mechanisms for the efficacy of IVIg in autoimmune diseases include the blockade of phagocytic cell Fc receptors; immunomodulation of lymphocyte differentiation and effector functions, including B-cell immunoglobulin production and T-cell suppressor activity; perturbation of inflammatory mediator or immunomodulator levels, including cytokines, chemokines, complement pathways, eicosanoids, steroids and neuropeptides; the solubilization of immune complexes; and anti-idiotypic manipulation of autoantibodies [27][28][29][30][31][32][33][34][35]. IVIg can also induce the production of interleukin-1 receptor antagonist and suppress the production of tumour necrosis factor-a and interleukins-1 and -6, thus providing a possible explanation for its beneficial effect in the treatment of conditions associated with fibrosis [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, neopterin estimations may under these circumstances be more useful than erythrocyte sedimentation rate (ESR) estimations, which has a long latency period (95).…”
Section: Comparison Of Neopterin Concentrations and Other Laboratory mentioning
confidence: 99%
“…Increased neopterin levels also followed withdrawal of cyclosporine A, since this drug inhibits secretion of interferon-g by T cells (27). A significant increase in plasma levels of neopterin was seen in patients with primary hypogammaglobulinaemia after one bolus injection (400 mg/kg) of intravenous immunoglobulin (IVIG) (95). A fast increase of neopterin values in sera of advanced cancer patients was seen during subcutaneous treatment with recombinant interleukin-2 (96).…”
Section: Influence Of Immunotherapy On Neopterin Levelsmentioning
confidence: 99%